2012
DOI: 10.1007/s10549-012-2169-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Dicer expression is associated with breast cancer progression and recurrence

Abstract: Dicer is a protein that plays a pivotal role in the final steps of the microRNA (miRNA) processing pathway, to produce mature miRNAs from their precursor molecules. The purpose of the current study was to assess the biological and prognostic value of Dicer protein expression in breast cancer (BC). Dicer protein expression was assessed immunohistochemically in two sets of BC: (1) full-face sections of selected BC series with distinct stages of tumour progression (normal, in situ (DCIS), primary invasive BC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 47 publications
5
66
1
1
Order By: Relevance
“…Dicer1 functions as a haploinsufficient tumor suppressor gene in Ptch1-induced medulloblastoma DICER1 has previously been reported to function as a haploinsufficient tumor suppressor gene in human tumors (Karube et al 2005;Chiosea et al 2007;Merritt et al 2008;Grelier et al 2009;Faggad et al 2010;Lin et al 2010;Khoshnaw et al 2012;Jafarnejad et al 2013) and genetically engineered mouse models (Kumar et al 2009;Lambertz et al 2010), with only a handful of exceptions (Arrate et al 2010;Sabbaghian et al 2012;Zhang et al 2013). The precise role of DICER1 in medulloblastoma is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Dicer1 functions as a haploinsufficient tumor suppressor gene in Ptch1-induced medulloblastoma DICER1 has previously been reported to function as a haploinsufficient tumor suppressor gene in human tumors (Karube et al 2005;Chiosea et al 2007;Merritt et al 2008;Grelier et al 2009;Faggad et al 2010;Lin et al 2010;Khoshnaw et al 2012;Jafarnejad et al 2013) and genetically engineered mouse models (Kumar et al 2009;Lambertz et al 2010), with only a handful of exceptions (Arrate et al 2010;Sabbaghian et al 2012;Zhang et al 2013). The precise role of DICER1 in medulloblastoma is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Global repression of miRNAs in human cancers has been observed in previous studies (11,12) and has been suggested to result from defective biogenesis machinery. Dysregulation of Dicer is of great interest because, similarly to the suppression of miRNA, downregulation of Dicer has been widely observed in many types of human tumors and Dicer has been shown to function as a tumor suppressor (12)(13)(14)(15)(16)(17). Suppression of Dicer expression was found to dramatically enhance cancer metastasis through miR-200 miRNA (15,18).…”
Section: Introductionmentioning
confidence: 99%
“…Dicer is an essential enzyme in miRNA biogenesis to its maturation, functionally active form able to regulate gene expression (41). Downregulation of Dicer has been shown to be associated with solid tumor progression in breast, ovarian, lung, and colorectal cancers (15,18,(42)(43)(44), whereas upregulation of Dicer has been observed in prostate and oral cancer (45,46). Although Sugito and colleagues reported that Dicer1 mRNA expression level did not exhibit significant associations with survival in patients with esophageal cancer (47), we observed that higher protein levels of Dicer in ESCC were associated with better clinical outcomes in patients with ESCC.…”
Section: Discussionmentioning
confidence: 99%